Small-cell lung carcinoma metastasis to the iris – case presentation - Nikratowicz, Danuta; Rospond-Kubiak, Iwona; Kocięcki, Jarosław (Contemporary Oncology/Współczesna Onkologia, 2013)
Introduction: Metastatic tumors are the most common intraocular malignancies in adults. Anterior segment metastases account for about 7.2–14.1% of all intraocular metastatic tumors with those to the iris representing 3.6–7.8% of the cases. Breast and lung are the most frequent primary sites of metastasizing cancer. The aim of this study is to present the case of a 43-year-old patient with a rare small-cell lung carcinoma metastasis to the iris. Case report : A patient with small-cell lung carcinoma and metastases in the brain who had been treated with chemo- and radiotherapy attended an outpatient clinic because of redness of her left eye. Based on the ophthalmological examination, a diagnosis of numerous metastatic tumors to the iris was made and the patient was referred for re-chemotherapy. Complete regression of the iris lesions was observed after 5 months but unfortunately two months later the patient died, due to progression of her systemic disease. Discussion : Among lung cancers, adenocarcinomas are much more likely to produce distant metastases to the iris than small-cell carcinomas [4]. More than 50% of patients with small-cell lung carcinoma have metastases in the brain. The survival rate in cases of lung cancer with eye involvement is poor and approximates to 7 months. However, since there is a strong probability of angle involvement and subsequent secondary glaucoma, the early onset of treatment can improve the patient’s quality of life during the terminal phase of the disease.